An investigation into the factors affecting second language learners’ classroom participation - Mohamad Nor, Faizah (2010)
This study was conducted to identify the second language learners' perceptions of their classroom participation. Factors influencing the learners' classroom participation were also examined. Besides, it also explored the lecturers' perceptions of the second language learners' participation in the classrooms. A group of 35 learners who enrolled in two classes and two lecturers who taught the classes were selected as the respondents of this study. The data for this study were obtained via questionnaires, observations, and interviews. The findings of this study show that a majority of the learners perceived that they were passive in classroom participation. This study also indicated the key factors restricting a majority of the learners' participation, which are affective, cognitive, cultural, learning strategies, and pedagogical factors. To be specific, students' fear of the lecturers' criticism towards their responses, anxiety, perception of the lecturers as the authority, reluctance to criticize their peers' opinions, fear of the lecturers' possibility of asking for elaboration, learning strategies, and the lecturers' teaching practices and personality significantly inhibited their participation. As for the lecturers, they perceived that the students were passive and the factors which may have caused the reticence are the learners' personality and their perceptions of their roles as universities students. Next, they reported that students' participation does not reflect their actual academic ability. The techniques used in stimulating learners' feedback were also identified. Pedagogical implications of this study and recommendations for future research were also made.